Risk Premium on the Short Rate Market - Comparison of the Polish and European Markets Behaviour During the Crisis - Kliber, Agata; Płuciennik, Monika (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
In the paper we investigate the risk premium on the Polish and European interbank markets based upon the LIBOR and OIS data. We compare the dynamics of the risk premia during the crisis period. The results of our analysis show that the risk premia on both markets reacted to the monetary policy movements. However, the results obtained for Poland clearly suggest the immaturity of the OIS market S
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 132-142
Keywords: kontrakty swap; stopa procentowa; premia za ryzyko; model GARCH; swap contracts; interest rate; risk premium; GARCH models